An Office Management Model for Higher Education Institutions in Thai Service Supply Chains - Artaphon Chansamut (ExcelingTech, 2023)
This research aim to design and evaluate an office management model for higher education institutions in Thai service supply chains Then, developed a survey research, which used the sample group consisted of five in supply chain, five experts in Management. All totalling ten experts. Data analysis was the average mean and standard deviation. The research was found that an office management model for higher education institutions in Thai service supply chains six comprises namely main components, Supplier, Manufacturer, Material handling and packaging, Service provider ,Customers and results from ten experts agreement of an office management model for higher education institutions in Thai service supply that mean an office management model for higher education institutions in Thai service supply chain to may be appropriately applied in actual work settings.